Train smarter, play more: Insights about preparation and game participation in youth national team - Arede, J.; Ferreira, A. P.; Esteves, P.; Gonzalo-Skok, O.; Leite, N. (Research Quarterly for Exercise and Sport, 2020)
Purpose: The aim of this study was to analyze the relationship between physical preparation, training sessions (TS) and friendly matches` (FM) demands, and playing status during European Championship (EC). Method: Twelve under-16 (U-16) basketball players performed physical (jumping, agility, aerobic fitness, and lower limb asymmetry index [ASI]) tests prior to attending the national team training camp. External training load was assessed using the WIMU PRO System put in place during TS (n = 19) and FM (n = 3), integrating the national team preparation. Perceptual response (RPE), muscle soreness (DOMS), and game-related statistics were also collected. Playing status during the U-16 EC (starters vs nonstarters) were taken into consideration to analyze the between-subjects differences across all variables. A stepwise discriminant analysis was computed to identify the construct that best differentiated the players` playing status (starters vs nonstarters) during the EC. Results: The starters were characterized by lower movement demands in both TS (ES: -0.02 to -1.26) and FM (ES: -0.03 to -1.94), however, outscored nonstarters in most FM-related statistics (ES: 0.10 to 3.62), with exception to blocks and rebounds. The number of high-intensity decelerations during FM (p = .05), but also training DOMS, number of steals, efficiency, minutes during FM, and countermovement jump (CMJ) (p = .01) substantially discriminated the playing status over the course of the EC. Conclusion: Game-related statistics obtained in FM seem to be a determinant aspect that increases the probability to be the starter during the EC.